Early treatment with nootkatone prevents pressure overload-induced ventricular remodeling and heart failure - Liu, Zhongyuan; Zhou, Zixin; Yuan, Wenjing; Li, Jiajin; Tian, Jie; Li, Mi; Quan, Junjun (Frontiers in Pharmacology, 2026)
Heart failure (HF) represents the clinical end stage of most cardiovascular diseases and remains a major cause of mortality, morbidity, and poor quality of life worldwide. In the present study, we use a mouse model induced by abdominal aortic constriction (AAC) that mimics HF and evaluate the potential therapeutic effects of nootkatone (NKT) on this model. Ejection fraction (EF) and fractional shortening (FS) progressively deteriorated in the AAC mice. The AAC mice were treated with NKT for 8 weeks starting on the eighth day post-AAC. Early NKT treatment prevented cardiac dysfunction in the AAC mice at 8 and 12 weeks after administration, along with thinner left ventricular posterior wall, lower left ventricular mass and ratio of heart weight/tibial length, and fewer cardiomyocyte areas. Furthermore, we found that NKT significantly reduced the expression levels of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), collagen types Ⅰ and Ⅲ, TGF-β1, Smad3, and the phosphorylation of Smad3. Furthermore, NKT decreased the activation of cardiac fibroblasts and myocardial fibrosis in the AAC mice. Our data suggest that NKT can delay or reverse the progression of HF after AAC and reduce myocardial hypertrophy and fibrosis possibly via inhibition of the TGF-β1/Smad3 signaling pathway.